Analisis Pertanggungjawaban Pidana terhadap Penganiayaan Ringan : (Studi Putusan Nomor 1748/Pid.B/2023/PN Lbp) - Jahtra Solin; Dani Sintara (International Forum of Researchers and Lecturers, 2024)
Abuse is a crime against the body (physical). The word abuse as stated in the Big Indonesian Dictionary (KBBI) is arbitrary treatment (torture, oppression, and so on). From this definition, it is expanded again in terms of meaning, namely concerning